2010
DOI: 10.1051/0004-6361/200913185
|View full text |Cite
|
Sign up to set email alerts
|

Molecular tracers of filamentary CO emission regions surrounding the central galaxies of clusters

Abstract: Context. Optical emission is detected from filaments around the central galaxies of clusters of galaxies. These filaments have lengths of tens of kiloparsecs. The emission is possibly due to heating caused by the dissipation of mechanical energy and by cosmic ray induced ionisation. CO millimeter and submillimeter line emissions as well as H 2 infrared emission originating in such filaments surrounding NGC 1275, the central galaxy of the Perseus cluster, have been detected. Aims. Our aim is to identify those m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 26 publications
0
22
1
Order By: Relevance
“…The infiltration of ICM X-ray gas into the molecular gas can reduce, through grain sputtering, the dust content, which in turn affects the H 2 formation rate and thus the [CO/H 2 ] abundance. As shown by Bayet et al (2010), highly energetic particles can have a significant effect on the chemistry of the molecular gas, altering the abundance of various molecules (although apparently not CO). The gas chemistry also depends on the gas temperature; in §5.1, we showed that the molecular gas traced by CO in NGC 1275 can have a higher characteristic temperature than that of Galactic GMCs.…”
Section: Turbulent Structuresmentioning
confidence: 99%
“…The infiltration of ICM X-ray gas into the molecular gas can reduce, through grain sputtering, the dust content, which in turn affects the H 2 formation rate and thus the [CO/H 2 ] abundance. As shown by Bayet et al (2010), highly energetic particles can have a significant effect on the chemistry of the molecular gas, altering the abundance of various molecules (although apparently not CO). The gas chemistry also depends on the gas temperature; in §5.1, we showed that the molecular gas traced by CO in NGC 1275 can have a higher characteristic temperature than that of Galactic GMCs.…”
Section: Turbulent Structuresmentioning
confidence: 99%
“…In the present work, the code is used to determine the chemical and thermal properties at all depths up to 20 visual magnitudes. For the present work, and consistent with the Bayet et al (2010) version of the code, additional radiative cooling due to rotational transitions of 13 CO, C 18 O, CS, OH and H 2 O have been implemented. The escape probability formalism of de Jong, Boland & Dalgarno (1980) is used to determine non‐local thermodynamic equilibrium level populations and resulting line intensities at each depth‐ and time‐step, in the same manner as for the existing coolants in the code.…”
Section: Model Descriptionmentioning
confidence: 99%
“…The ucl_pdr code also includes cooling due to the O i metastable levels, and the O–H + collisions and O–e collisions which excite them; these are important for the models for high values of ζ. The treatment of H 2 self‐shielding has also been updated to use the results of detailed calculations performed by Lee et al (1996), as described in Bayet et al (2010). The chemical network links 131 species in over 1834 gas‐phase reactions; only H 2 is formed by surface chemistry; freeze‐out of species on to grain surfaces is excluded.…”
Section: Model Descriptionmentioning
confidence: 99%
“…In modeling cooling, both methods include emission by C, C + , and O fine structure lines, gas-grain collisional cooling, cooling by rotational lines of CO, and H 2 collisional dissociation, but 3d-pdr neglects H 2 and H 2 O ro-vibrational and OH rotational lines, which are included in the one-dimensional code ucl_pdr (Bayet et al 2010), as well as H collisional ionization and Compton cooling. However, these lines do not produce significant cooling under the conditions considered here, and so neglecting them is a good approximation.…”
Section: Code Comparison: Post-processing Versus In Situ Calculationmentioning
confidence: 99%